Letters from the boys : Wisconsin World War I soldiers write home - Meyer, Carrie A. (Wisconsin Historical Society Press, 2018)
"On the 100th anniversary of the arrival of the flood of American troops in Europe that would shift the tide of World War I in favor of the Allies, Letters from the Boys brings to life once again this terrible war as experienced by Wisconsinites who wrote home to local newspapers. Technology had transformed the battlefield in alarming ways. Automatic rifles mowed down, at an astonishing rate, the young men who went "over the top" to attack enemy trenches; airplanes and improved artillery brought death unseen from miles away; poison gas choked and burned as terrifying clouds moved through the European countryside; the internal combustion engine brought tanks to the battlefield for the first time and revolutionized the way troops moved about and the wounded were recovered and transported to get help. Watching and experiencing all of this were young men from Wisconsin who found themselves caught up in geopolitical events half a world away. Professor Carrie A. Meyer combed through three newspapers in Green County, Wisconsin, to collect and synthesize the letters from the boys into a narrative that is both unique and representative, telling the stories of several Green County boys and what they saw, from preparing for war, to life among French families near the front, to the terror of the battlefield. Meyer gracefully removes the veil of obscurity and anonymity hanging over soldiers who participated in a war fought so long ago by great numbers of men, reminding us that armies are made of individuals who strove to do their part then return to their families"--